2018
DOI: 10.1016/j.snb.2018.08.137
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell electro-phenotyping for rapid assessment of Clostridium difficile heterogeneity under vancomycin treatment at sub-MIC (minimum inhibitory concentration) levels

Abstract: Current methods for measurement of antibiotic susceptibility of pathogenic bacteria are highly reliant on microbial culture, which is time consuming (requires > 16 hours), especially at near minimum inhibitory concentration (MIC) levels of the antibiotic. We present the use of single-cell electrophysiology-based microbiological analysis for rapid phenotypic identification of antibiotic susceptibility at near-MIC levels, without the need for microbial culture. Clostridium difficile (C. difficile) is the single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Importantly, we note that the advantage of using some of these indicators alternative to growth is also supported by other findings which do not necessarily use photonics, such as microfluidic techniques [25,119,133,134], AFM cantilever deflection [24,120,135] or electrochemical platforms [136][137][138]. For example, bacterial metabolism drives ionexchange across the membrane, so we see the measurement of electrical impedance at the single-cell level as a very promising method that could be added to the toolkit [90,136].…”
Section: Discussionsupporting
confidence: 60%
“…Importantly, we note that the advantage of using some of these indicators alternative to growth is also supported by other findings which do not necessarily use photonics, such as microfluidic techniques [25,119,133,134], AFM cantilever deflection [24,120,135] or electrochemical platforms [136][137][138]. For example, bacterial metabolism drives ionexchange across the membrane, so we see the measurement of electrical impedance at the single-cell level as a very promising method that could be added to the toolkit [90,136].…”
Section: Discussionsupporting
confidence: 60%
“…Dielectrophoresis and cellular impedance spectroscopy have demonstrated a capability to differentiate cells based upon changes in the biochemical makeup of the cellular structure with labels (Labeed et al, 2003(Labeed et al, , 2011Chin et al, 2006;Coley et al, 2007;Flanagan et al, 2008;Jones et al, 2015;Su et al, 2016;Fernandez et al, 2017;Rohani et al, 2018;Crowther et al, 2019;Liu et al, 2019; Hilton et al, 2020). When fully developed and vetted, this approach of serotyping will require less expense and expertise compared to producing antisera in agglutination test utilizing O and H antiserum and will not require expert genomic information interpretation skills in whole genome sequencing for identifying Salmonella (Ng and Kirkness, 2010;Ashton et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…They found increased intracellular lipid content resulted in decreased conductivity as well as decreased permittivity of cytoplasm [79]. Rohani et al demonstrated through DEP observation and ROT measurement that cytoplasmic conductivity alterations could quantify persistent live Clostridium difficile (C. difficile) after treatment [80]. Parameters for the cell envelope and cytoplasm of highly toxigenic (HTCD), low toxigenic (LTCD), and nontoxigenic (NTCD) samples were determined.…”
Section: Dep Characterization Methods and Parametersmentioning
confidence: 99%
“…Previously mentioned, Han et al found increased intracellular lipid content resulted in decreased conductivity as well as decreased permittivity of cytoplasm in microalgae [79]. Rohani et al demonstrated that cytoplasmic conductivity alterations could quantify persistent live Clostridium difficile ( C. difficile ) after treatment [80]. This measurement as an indicator of antimicrobial resistance just 4 h after treatment presents a much more rapid measurement to the standard microbiological growth rate or secreted metabolite toxin which require 24 h of culture to identify persistent C. difficile subpopulations, and with no ability for its quantification.…”
Section: Dep Characterization Methods and Parametersmentioning
confidence: 99%